Sustainable development across central and eastern Europe: key factors driving the economic growth of the countries - Lapinskienė, Giedrė; Tvaronavičienė, Manuela (Business: Theory and Practice, 2009)
Sustainable development is the leading concept of our days, and it is measured by a number of various indicators. The paper analyses sustainable development indicators (Eurostat database), taking Central and Eastern Europe as the research object. The suggested hypothesis implies that, in a particular region, there might be a set of sustainable development indicators reflecting the factors strongly influencing GDP. The results obtained outline the main issues relating to economic development of Lithuania and other Central and Eastern European countries and demonstrate similar development trends in the region. Darnusis vystymasis centrinėje ir Rytų Europoje: pagrindiniai ekonominio augimo aspektai Santrauka. Šiuo metu darnusis vystymasis yra pagrindinė ilgalaikė visuomenės vystymosi ideologija. Ji gali būti vertinama įvairiais rodikliais. Straipsnyje analizuojami Centrinės ir Rytų Europos darniojo vystymosi rodikliai (Eurostat duomenų bazė). Remiantis iškelta hipoteze, tam tikrame regione turėtų būti išskirtiniai darniojo vystymosi rodikliai, darantys didžiausią poveikį ekonominiam augimui. Gauti rezultatai pabrėžia pagrindines sritis, darančias įtaką ekonominiam vystymuisi Lietuvoje ir kitose Centrinės bei Rytų Europos šalyse, atskleidžia panašias vystymo tendencijas regione. Reikšminiai žodžiai: darnusis vystymasis, ekonominis augimas (BVP), Centrinė ir Rytų Europa, Lietuva. First published online: 22 Sep 2009